The interaction between history' and story' in Roman historiography: the rhetorical construction of the historical image of Nero - Kugelmeier, Christoph (Church, Communication and Culture, 2019)
This paper examines the way in which ancient historiography makes use of rhetorical and even fictional devices (dramatic poetry as well as the novel) to dramatize in writing down events which the historians obviously consider as being important for their judgement, ideologically or otherwise biased, of historical personalities. An outstanding example for this narrative method is the Roman author most often thought of as one of the greatest historians in all antiquity: Tacitus. It can be shown that he in those of the books of his Annals which concern the reign of Nero makes use of rumours, insinuations and even fictional elements, especially of the ancient novel and novella (examples for this will be taken mostly from Ann. XIII-XVI), and particularly with regard to Nero's relationship with his mother, Agrippina.